Assessing the biodegradability of microparticles disposed down the drain. (May 2017) - McDonough, Kathleen; Itrich, Nina; Casteel, Kenneth; Menzies, Jennifer; Williams, Tom; Krivos, Kady; Price, Jason
Abstract: Microparticles made from naturally occurring materials or biodegradable plastics such as poly(3-hydroxy butyrate)-co-(3-hydroxy valerate), PHBV, are being evaluated as alternatives to microplastics in personal care product applications but limited data is available on their ultimate biodegradability (mineralization) in down the drain environmental compartments. An OECD 301B Ready Biodegradation Test was used to quantify ultimate biodegradability of microparticles made of PHBV foam, jojoba wax, beeswax, rice bran wax, stearyl stearate, blueberry seeds and walnut shells. PHBV polymer was ready biodegradable reaching 65.4 ± 4.1% evolved CO2 in 5 d and 90.5 ± 3.1% evolved CO2 in 80 d. PHBV foam microparticles (125–500 μm) were mineralized extensively with >66% CO2 evolution in 28 d and >82% CO2 evolution in 80 d. PHBV foam microparticles were mineralized at a similar rate and extent as microparticles made of jojoba wax, beeswax, rice bran wax, and stearyl stearate which reached 84.8  ± 4.8, 84.9  ± 2.2, 82.7  ± 4.7, and 86.4 ± 3.2% CO2 evolution respectively in 80 d. Blueberry seeds and walnut shells mineralized more slowly only reaching 39.3  ± 6.9 and 5.1 ± 2.8% CO2 evolution in 80 d respectively. Graphical abstract: Highlights: OECD 301B Ready Biodegradation method adapted for non-soluble microparticles. Significant mineralization observed for PHBV foam microparticles. Significant mineralization jojoba wax, beeswax, rice bran wax, stearyl stearate. Blueberry seeds and walnut shells limited mineralization at study completion.